2007
DOI: 10.1080/13561820601095800
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional training in clinical practice on a training ward for healthcare students: A two-year follow-up

Abstract: This follow-up study describes the former students' lasting impressions of a two-week interprofessional course on a training ward aimed at enhancing the understanding of the roles of other professions and the importance of communication for teamwork and for patient care as well as providing an opportunity for profession-specific training. A questionnaire with both closed and open-ended questions was sent to 633 former students two years after the course and 348 (55%) responded. The course was rated as very goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 8 publications
5
77
1
7
Order By: Relevance
“…The combination of quantitative and qualitative results in this study, in which the results support and strengthen each other, makes the results transferable to other similar settings, and this can be further validated by similar results found earlier (Fallsberg & Wijma 1999;Ponzer et al 2004;Hylin et al 2007). …”
Section: Methodssupporting
confidence: 73%
See 1 more Smart Citation
“…The combination of quantitative and qualitative results in this study, in which the results support and strengthen each other, makes the results transferable to other similar settings, and this can be further validated by similar results found earlier (Fallsberg & Wijma 1999;Ponzer et al 2004;Hylin et al 2007). …”
Section: Methodssupporting
confidence: 73%
“…Difficulties in developing professional roles and professional identities together with too few profession-specific tasks are a risk when blurring the professional roles by letting medical students take part in general patient care (Hylin et al 2007). …”
Section: Interprofessional Collaborationmentioning
confidence: 99%
“…Most research into interprofessional learning on placement has explored learning opportunities that were organised in advance, for example interprofessional training wards (Freeth et al 2002, Hylin et al 2007, Mackenzie et al 2007, Smith & Seeley 2010, O'Carroll et al 2012. In contrast interprofessional peer feedback opportunities identified in this study were mostly opportunistic.…”
Section: Learning From Other Disciplinesmentioning
confidence: 50%
“…At a personal level, through engagement in interprofessional peer feedback, a number of students reported increased confidence, and a deeper understanding of each other's roles (Stew 2005, Hylin et al 2007, Steven et al 2007; they valued discussion with their interprofessional peers which helped them to view their own practice from a different perspective. Most research into interprofessional learning on placement has explored learning opportunities that were organised in advance, for example interprofessional training wards (Freeth et al 2002, Hylin et al 2007, Mackenzie et al 2007, Smith & Seeley 2010, O'Carroll et al 2012.…”
Section: Learning From Other Disciplinesmentioning
confidence: 99%
“…Interestingly several authors have reported on the training of clinical teachers for teaching in IPE courses (Anderson, Manek, and Davidson 2006, Hunter et al 2008, Hylin et al 2007, Jacobsen et al 2009, Kinnair, Anderson, and Thorpe 2012. Others have suggested key skills required (Freeman, Wright, and Lindqvist 2010, Banfield and Lackie 2009, Harvey et al 2002.…”
Section: Literature Reviewmentioning
confidence: 99%